Les voix à l’œuvre dans la narration de la Shoah - Béatrice Finet (Strenae)
Children’s stories about the Holocaust are about transmission, presenting both an identified narrator and characters whose memories must be preserved. The Holocaust, embodied in the writing of these narratives, gives an account of the destruction and incomprehension of the victims, thus calling for a particular narration characterized by several narrators present in and outside the text. Walter Benjamin's philosophy on the subject of the narrator, as well as the distinction he makes between fixed memory of a novel and memory in motion within a narrative, allows us to think about the singularity of these writings, which have a well-defined social function—to speak of the Holocaust to children—in order to impart the memories of it.